2003
DOI: 10.1074/jbc.m208310200
|View full text |Cite
|
Sign up to set email alerts
|

Deleted in Liver Cancer (DLC) 2 Encodes a RhoGAP Protein with Growth Suppressor Function and Is Underexpressed in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a major malignancy in many parts of the world, especially in Asia and Africa. Loss of heterozygosity (LOH) on the long arm of chromosome 13 has been reported in HCC. In search of tumor suppressor genes in this region, here we have identified DLC2 (for deleted in liver cancer 2) at 13q12.3 encoding a novel Rho family GTPase-activating protein (GAP). DLC2 mRNA is ubiquitously expressed in normal tissues but was significantly underexpressed in 18% (8/ 45) of human HCCs. DLC2 is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
228
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(239 citation statements)
references
References 47 publications
(56 reference statements)
7
228
1
Order By: Relevance
“…The gene DLC-2 was also recently shown to be homologous to DLC-1, to be underexpressed in HCC, and to inhibit Ras-induced transformation of rodent cells (Ching et al, 2003).These results clearly indicate that Rho-GAP protein has growth inhibitory and antineoplastic effect in the early stages in neoplastic transformation. The negative regulatory activity of Rho-GAP proteins on cell growth is thought to be attributable to their ability to downregulate the GTPase activity of Rho family proteins.…”
Section: Discussionsupporting
confidence: 52%
“…The gene DLC-2 was also recently shown to be homologous to DLC-1, to be underexpressed in HCC, and to inhibit Ras-induced transformation of rodent cells (Ching et al, 2003).These results clearly indicate that Rho-GAP protein has growth inhibitory and antineoplastic effect in the early stages in neoplastic transformation. The negative regulatory activity of Rho-GAP proteins on cell growth is thought to be attributable to their ability to downregulate the GTPase activity of Rho family proteins.…”
Section: Discussionsupporting
confidence: 52%
“…Among sterile alpha motif (SAM), RhoGAP and steroidogenic acute regulatory (StAR)-related lipidtransfer (START) domains, three major functional domains contained in DLC-1 and its family members (Ching et al, 2003), the RhoGAP domain appears most likely to be responsible for DLC-1-mediated antitumor activity. Other examples of the involvement of RhoGAP genes in human cancer development include GRAF, which is deleted or mutated in myelodysplastic syndromes, and the p190-A gene, which is located in a region of deletion and recombination in gliomas and astrocytomas (Borkhardt et al, 2000;Tikoo et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…One subgroup of the human RhoGAPs includes DLC-1 (deleted in liver cancer 1), the human homologue of rat p122RhoGAP (Homma and Emori, 1995;Yuan et al, 1998), and DLC-2, also known as STARD13 . The DLC-1 and DLC-2 genes encode polypeptides of approximately 1100 amino acids (aa) with a characteristic modular architecture, consisting of an N-terminal sterile a motif (SAM) domain, a serine-rich domain, a RhoGAP domain and a C-terminal steroidogenic acute regulatory protein-related lipid transfer (START) domain (Homma and Emori, 1995;Yuan et al, 1998;Ponting and Aravind, 1999;Ching et al, 2003). DLC-1 and DLC-2 were shown to have in vitro GAP activity for RhoA and Cdc42 and to influence cell morphology and cytoskeletal organization (Homma and Emori, 1995;Sekimata et al, 1999;Ching et al, 2003;Wong et al, 2003Wong et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The DLC-1 and DLC-2 genes encode polypeptides of approximately 1100 amino acids (aa) with a characteristic modular architecture, consisting of an N-terminal sterile a motif (SAM) domain, a serine-rich domain, a RhoGAP domain and a C-terminal steroidogenic acute regulatory protein-related lipid transfer (START) domain (Homma and Emori, 1995;Yuan et al, 1998;Ponting and Aravind, 1999;Ching et al, 2003). DLC-1 and DLC-2 were shown to have in vitro GAP activity for RhoA and Cdc42 and to influence cell morphology and cytoskeletal organization (Homma and Emori, 1995;Sekimata et al, 1999;Ching et al, 2003;Wong et al, 2003Wong et al, , 2005. DLC-1 inhibits the growth, colony-forming ability, tumorigenicity and invasiveness of human liver, breast, ovarian, nasopharyngeal, esophageal and nonsmall cell lung cancer cells (Ng et al, 2000;Yuan et al, 2003Yuan et al, , 2004Zhou et al, 2004;Goodison et al, 2005;Syed et al, 2005;Wong et al, 2005;Seng et al, 2006), and DLC-2 has been shown to inhibit the ras-induced transformation of rodent cells and the growth of breast and liver cancer cells in culture (Nagaraja and Kandpal, 2004;Leung et al, 2005).…”
Section: Introductionmentioning
confidence: 99%